2020
DOI: 10.1371/journal.pone.0234673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a large-scale flow manipulation to the upper San Francisco Estuary: Response of habitat conditions for an endangered native fish

Abstract: While flow is known to be a major driver of estuarine ecosystems, targeted flow manipulations are rare because tidal systems are extremely variable in space and time, and because the necessary infrastructure is rarely available. In summer 2018 we used a unique water control structure in the San Francisco Estuary (SFE) to direct a managed flow pulse into Suisun Marsh, one of the largest contiguous tidal marshes on the west coast of the United States. The action was designed to increase habitat suitability for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…The results of this study and Sommer et al (2020) indicate that the SMSCG operations and flow pulse altered aquatic habitat in Suisun Marsh. Examining long-term data from fisheries monitoring programs revealed limited impacts on the overall aquatic community structure but FIGURE 6.…”
Section: Estuarine Response To Large-scale Flow Managementmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of this study and Sommer et al (2020) indicate that the SMSCG operations and flow pulse altered aquatic habitat in Suisun Marsh. Examining long-term data from fisheries monitoring programs revealed limited impacts on the overall aquatic community structure but FIGURE 6.…”
Section: Estuarine Response To Large-scale Flow Managementmentioning
confidence: 62%
“…We found that implementation of the SMSCG action and coincident flow pulse resulted in a clear and rapid decline in salinity within the marsh. Results from this study and from Sommer et al (2020) have important management implications due to the role of salinity in shaping aquatic food webs and species assemblages in estuaries (Barletta et al 2005;Bernhard et al 2007). Although the salinity changes were not extreme, earlier research suggested that broad guilds of species in the Bay-Delta respond strongly to shifts in regional salinity (Feyrer et al 2015); hence, the observed changes had the potential to affect broader community patterns.…”
Section: Discussionmentioning
confidence: 85%
“…Examples of targeted flow actions in the San Francisco Estuary include: (1) managed seasonal inundation experiments in Yolo Bypass to support native fish rearing (Katz et al 2017;Sommer et al , 2020b; (2) a summer 2018 effort to direct more low-salinity flow into Suisun Marsh-a key region in the system for many species-using a unique water control structure (Sommer et al 2020a); and (3) the North Delta flow action described in the current study. However, there is a major conceptual difference between the Suisun Marsh (Sommer et al 2020a) and Yolo Bypass (Sommer et al 2008(Sommer et al , 2020b experiments and the current effort. The North Delta flow action represents a rare but increasingly important example of a targeted action in a specific geographic region of the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Overview. As a test application for this algorithm as an evaluation tool, we used this approach to examine water quality changes during a novel 2018 flow action to support Delta Smelt (California Natural Resources Agency 2016; Sommer et al 2020). CDWR lead a pilot study in collaboration with multiple agencies.…”
Section: Analysis Of Turbidity During Suisun Marsh Salinity Control Gates Action ("Gates Action")mentioning
confidence: 99%
“…While CDWR did not expect that the action would change turbidity in any of the regions, we examined spatial and temporal patterns to see if there was evidence of differences following the action. Sommer and colleagues describe outcomes in more detail, observing an overall improvement in habitat quality with a focus on salinity and other biological metrics (Sommer et al 2020). The following sections describe our approach toward examining the variability of turbidity most likely associated with the Gates action while accounting for tidal stage and height.…”
Section: Analysis Of Turbidity During Suisun Marsh Salinity Control Gates Action ("Gates Action")mentioning
confidence: 99%